The concept of a digital transformation of a traditional university to a “digital university” - G. Kuzina (State University of Management, 2020)
One of the priorities of the government program “Digital economy of the Russian Federation” is the progressive development of the existing education system, which should provide the economy with competent personnel. In addition, this document declares the need to create a system of motivation for the development of the necessary competencies and participation of personnel in the development of the digital economy of Russia. All this requires the transformation of the classical educational system, which ultimately implies the creation of a “digital university”.According to the concept, proposed by the Agency for Strategic Initiatives together with Skolkovo University, the “digital university” will allow us to change the form and content of education in accordance with the requirements for new digital economy personnel. At the same time, the main emphasis should be placed on the individual trajectory of education, that is, collecting information not only according to the teacher’s assessment, but also collecting information in the student’s online course (what subjects the student was interested in, how he passed the intermediate tests, etc.). In addition, you need to create a specific set of services at the university. They should work in a similar way to the super services that are already being created in the Ministry of Digital Development, Communications and Mass Media of the Russian Federation for receiving public services online. So, the student will be able to get help and get registered in the military enlistment office in a single window mode, without having to go to the offices. In addition, changes are needed related to the content of education. So, along with the already developing segment of mass online courses, courses using AR and VR and virtual simulators should be introduced in universities. With the help of modern technologies, students will be able to learn the profession more effectively in practice.The article attempts to generalize the minimum set of necessary transformations of a classical university into a “digital” one and present their description.